Smart Library Service Based on Quick Response Code on Smartphone - Edi Daenuri Anwar; Muhammad Ardhi Khalif; Andika Rifki Maulana; Ahmad Minanur Rohim (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a QR Code-based Smart Library software as a valid library service so that it can be used optimally in supporting library collection search and management activities. This Smart Library development research uses the Research and Development (R&D) method with the Unified Modeling Language (UML) development approach. The stages of this research include problem identification, data collection, system design, program creation, and testing stages. At the creation stage, the QR Code was developed using Quick Response Code Maker which was then integrated into the digital library system. The main software in the development of this Smart Library was built using Android Studio. Supporting facilities owned by Smart Library include the ability to display book collection metadata, display a list of collections based on the shelf number searched, and provide access to e-books from the library collection. This system also allows users to scan QR Codes directly via smartphones to get detailed information about available books. The results of the system test show that all application activities and performance run well and are in accordance with their functional needs. This QR Code-based Smart Library application program can produce output as expected and has fulfilled the basic functions of a smart library-based library service. Therefore, this QR Code-based Smart Library software development system is declared valid and suitable for use as an efficient library service solution.